(untitled) (International Journal of Innovative Technologies in Economy, 2021)
As the global epidemic continues to have an impact on the world economy and public health, the issue of climate change is still the core threat facing the world. The "2020 Global Risk Report" issued by the World Economic Forum (WEF) pointed out that the five major risks facing the world in the next 10 years are all related to the environment. A study on this pointed out: If governments adopt greener economic recovery plans, the world can reduce the temperature rise by 0.3°C by the middle of this century. In other words, accelerating green economic growth after the epidemic and promoting green transformation in all aspects have become the top issues facing countries. Some of the economic recovery plans proposed by Western Europe, South Korea, Canada and other countries may have a positive effect on the environment. Economic stimulus plans such as China, the United States, Australia, Italy, and Japan will invest most of the funds in non-green areas. Among them, the US economic stimulus plan may the negative environmental impact is the greatest. The Dubai’s World Green Economy Summit held this year undoubtedly produced a revolutionary change in thinking for the largest developing country like China.